International political communication and influence of information and communication technologies on contemporary international relations - Vranješ, Aleksandar; Budimir, Željko (Politeia, 2017)
International political communication can be seen as an auxiliary but also constitutive discipline of the International relations in the wider field of the Political science. At the very core of International relations is Political communication through which the most important actors of world politics realize political goals. This paper presents a short genesis of the development of the International political communication and relation to the International relations. The key terms have been defined, the most important theories have been given and today's global character of International communication has been highlighted. The changes in International politics were analyzed as the consequence of the information and communication revolution and the emergence of modern Information and communication technologies that change the very nature of International relations. An overview of the new communication technologies impact on the main actors (subjects/entities) of International relations was made, thus analyzing the impact of this factor on both state and non-state actors. We looked back at the impact of information and communication technologies on an individual who, thanks to the global communications network, became a real actor of world politics. There is also a section of the main theories of International relations and their relation to the challenges brought by the Informatics revolution (IT revolution) and the Digital age.